Expression patterns of microRNAs associated with CML phases and their disease related targets - Machová Poláková, Kateřina; Lopotová, Tereza; Klamová, Hana; Burda, Pavel; Trněný, Marek; Stopka, Tomáš; Moravcová, Jana (Molecular cancer, 2011)
BACKGROUND: MicroRNAs are important regulators of transcription in hematopoiesis. Their expression deregulations were described in association with pathogenesis of some hematological malignancies. This study provides integrated microRNA expression profiling at different phases of chronic myeloid leukemia (CML) with the aim to identify microRNAs associated with CML pathogenesis. The functions of in silico filtered targets are in this report annotated and discussed in relation to CML pathogenesis. RESULTS: Using microarrays we identified differential expression profiles of 49 miRNAs in CML patients at diagnosis, in hematological relapse, therapy failure, blast crisis and major molecular response. The expression deregulation of miR-150, miR-20a, miR-17, miR-19a, miR-103, miR-144, miR-155, miR-181a, miR-221 and miR-222 in CML was confirmed by real-time quantitative PCR. In silico analyses identified targeted genes of these miRNAs encoding proteins that are involved in cell cycle and growth regulation as well as several key signaling pathways such as of mitogen activated kinase-like protein (MAPK), epidermal growth factor receptor (EGFR, ERBB), transforming growth factor beta (TGFB1) and tumor protein p53 that are all related to CML. Decreased levels of miR-150 were detected in patients at diagnosis, in blast crisis and 67% of hematological relapses and showed significant negative correlation with miR-150 proved target MYB and with BCR-ABL transcript level. CONCLUSIONS: This study uncovers microRNAs that are potentially involved in CML and the annotated functions of in silico filtered targets of selected miRNAs outline mechanisms whereby microRNAs may be involved in CML pathogenesis.
Keywords: Humans; anotace sekvence; Down-Regulation; MicroRNAs; geny myb; Female; Cluster Analysis; Genes, myb; lidé; down regulace; reprodukovatelnost výsledků; ženské pohlaví; Male; Reproducibility of Results; chronická myeloidní leukemie; stanovení celkové genové exprese; regulace genové exprese u leukemie; shluková analýza; Molecular Sequence Annotation; mikro RNA; Gene Expression Profiling; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; mužské pohlaví; Gene Expression Regulation, Leukemic